Ações de gestão e práticas pedagógicas: construindo pontes e aproximando caminhos - Vaiteka, Sandra (Universidade do Vale do Rio dos Sinos, 2018)
This research has the proposition to demonstrate the relationship between school management and teacher’s activities. The main objective was to analyze potential connections amid managers’ actions in the school and teachers’ job. The focus, from this research standpoint, was to find possibilities to approach school management actions to teacher’s activities. The theoretical foundation endeavor to present the path to the concept of Educational Management – based on School Administration – reaching particularities of School Management based on Teixeira (1956), Gandin and Lima (2016), Apple (1999), Luck (2015) and Sander (2007). Ratio Studiorum and PEC (Projeto Educativo Comum) analysis were also used as documental references to the extent they both represent a precept of Jesuit Education. The methodology used was a quantitative and qualitative research carried out in a school belonging to Jesuit Educational Organization and to the purpose of data collection five directors were interviewed and 46 teachers responded to specific questionnaires. To analyze referred interviews Content Analysis technique in association to Conceptual Maps was used and specifically to questionnaires the answers were based on Likert scale.We concluded teachers want to be heard and considered in Managers’ decisions and this was the highest convergent point for both groups. The routine and time management are challenges for the managers who want to have more strategic activities. For the teachers, routine and time management are not as crucial as for the managers.The intervention proposal considered in this research indicates a systematic and non-episodic training for managers where these professionals can learn formal aspects from management, considering their own expertise, and then converting into institutional knowledge.
Keywords: Gestão Educacional; Gestão Escolar; Educação Básica; Educational Management; School Management; Basic Education; ACCNPQ::Ciências Humanas::Educação